2004
DOI: 10.1590/s1516-35982004000200006
|View full text |Cite
|
Sign up to set email alerts
|

Componentes de (co)variância e parâmetros genéticos de caracteres pós-desmama em bovinos da raça Angus

Abstract: RESUMO -Foram determinados os componentes de (co)variância para caracteres do período pós-desmama na raça Angus e de covariância com peso ao nascer (PN) e caracteres do período pré-desmama por intermédio de um modelo animal. Utilizaram-se dados de 18.921 animais com registros de peso à desmama e ao sobreano, dos quais 4.452 tinham avaliações completas para escores visuais à desmama e ao sobreano. Registros de PN estavam disponíveis para 11.788 animais. As herdabilidades do ganho de peso pós-desmama (GP205) e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
1
24

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 10 publications
(15 reference statements)
7
20
1
24
Order By: Relevance
“…This hypothesis is supported by the environmental correlation estimate between GBW and GWY (20.17 6 0.016; Table 5), indicating weak antagonism between environmental and non-additive genetic effects that act on the two traits. However, this result agrees with Cardoso et al (2004), Marcondes et al (2000) and Sarmento et al (2003) who reported genetic correlation estimates of 0.23, 0.23 and 0.22, respectively, between pre-and postweaning weight gains.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This hypothesis is supported by the environmental correlation estimate between GBW and GWY (20.17 6 0.016; Table 5), indicating weak antagonism between environmental and non-additive genetic effects that act on the two traits. However, this result agrees with Cardoso et al (2004), Marcondes et al (2000) and Sarmento et al (2003) who reported genetic correlation estimates of 0.23, 0.23 and 0.22, respectively, between pre-and postweaning weight gains.…”
Section: Resultssupporting
confidence: 91%
“…Similar genetic correlations have been reported by Koury Filho (2001) for Nelore animals. In contrast, Cardoso et al (2004) estimated higher correlations for Angus cattle.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations